Public scenic beauty preferences of highland environment - Othman, Jamilah (Medinanet.org, 2012)
This paper presents scenic beauty assessment of highland environment, in which the study area was Cameron Highlands, Malaysia. There were two methods used in the assessment; photographic questionnaire survey and semi structured interview. Both methods were designed to assess public scenic preferences and the impacts of Highland Management Practices (HMPs) on scenic preferences. Coloured photograph was the survey instrument used to assess the scenic preferences.